Economies of Scale and the Profitability of Marginal-Cost Pricing: A Note - Scott, John T. (Quarterly Journal of Economics, 1979)
Journal Article Economies of Scale and the Profitability of Marginal-Cost Pricing: A Note Get access John T. Scott John T. Scott Dartmouth College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 93, Issue 4, November 1979, Pages 741–742, https://doi.org/10.2307/1884482 Published: 01 November 1979